Maternal Serum Angiopoietin-Like 3 Levels in Healthy and Mild Preeclamptic Pregnant Women - Garces, María Fernanda; Rodriguez - Navarro, Haiver Antonio; Buell - Acosta, Julieth Daniela; Burgos - Cardenas, Alvaro Javier; Franco - Vega, Roberto; Maldonado - Acosta, Luis Miguel; Eslava - Schmalbach, Javier; Parada - Baños, Arturo José; Castro - Pinzon, Andres; Sanchez, Elizabeth; Angel - Muller, Edith; Lacunza, Ezequiel; et al. (Frontiers in Endocrinology, 2021)
Objective: Angiopoietin-like protein 3(ANGPTL3) is an important regulator of lipoprotein metabolism in the fed state by inhibiting the enzyme lipoprotein lipase in oxidative tissues. However, the possible role of ANGPTL3 throughout gestation and its relationship with hormonal and biochemical variables are still unknown. The aim of this study was to determinate serum ANGPTL3 level in healthy non-pregnant women, during healthy and preeclamptic pregnancy and postpartum. Methods: Serum ANGPTL3 was analyzed by enzyme-linked immunosorbent assay (ELISA), in a prospective cohort of healthy pregnant women (n = 52) and women with mild preeclampsia (n = 21), and women at three months postpartum (n = 20) and healthy non-pregnant women (n = 20). The results obtained were correlated with biochemical, hormonal and anthropometric variables and insulin resistance indices. Results: Levels of ANGPTL3 were not different between the follicular and the luteal phases of the cycle in healthy non-pregnant women. There was a significant reduction in serum ANGPTL3 levels from the first to the third trimester in healthy pregnant women compared with healthy non-pregnant and postpartum women (p <0.01). ANGPTL3 levels do not differ significantly during the three trimesters of pregnancy neither in healthy women nor in preeclamptic women. The serum levels of ANGPTL3 in women who developed preeclampsia are not statistically different from those observed in healthy pregnant women in each trimester of pregnancy. A significant lineal positive correlation was observed between serum ANGPTL3 levels and triglyceride (P =0.0186, r =0.52), very low-density lipoprotein cholesterol (P =0.0224, r =0.50), and total cholesterol levels (P =0.0220, r =0.50) in healthy non-pregnant women (P 0.05). Besides, there were no significant correlations between serum ANGPTL3 and body mass index (BMI), high-density lipoprotein cholesterol, glucose, insulin, leptin, or HOMA-IR (P >0.05) Conclusions: We describe for the first time the profile of ANGPTL3 throughout pregnancy and postpartum as well as and discussed about explore their potential contribution interactions with lipoprotein metabolism throughout pregnancy and postpartum. Thus, low levels of ANGPTL3 during pregnancy might favor lipid uptake in oxidative tissues as the main maternal energy source, while may helping to preserve glucose for use by the fetus and placenta.